Optimal insurance: Dual utility, random losses and adverse selection - Alex Gershkov; Benny Moldovanu; Philipp Strack; Mengxi Zhang (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2023)
We study a generalization of the classical monopoly insurance problem under adverse selection (see Stiglitz [1977]) where we allow for a random distribution of losses, possibly correlated with the agent's risk parameter that is private information. Our model explains patterns of observed customer behavior and predicts insurance contracts most often observed in practice: these consist of menus of several deductible-premium pairs, or menus of insurance with coverage limits-premium pairs. A main departure from the classical insurance literature is obtained here by endowing the agents with risk-averse preferences that can be represented by a dual utility functional (Yaari [1987]).
Keywords: 330; Versicherungsökonomik; Adverse Selektion; Risikoaversion; Asymmetrische Information